2022
DOI: 10.1186/s12957-022-02780-2
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of additional surgery for early gastric cancer in the upper third of the stomach meeting non-curative resection criteria after endoscopic submucosal dissection

Abstract: Background Additional surgery is recommended after non-curative endoscopic submucosal dissection for early gastric cancer. However, it is not easy to recommend for tumors located in the upper third of the stomach, because it would be a total or proximal gastrectomy. This study aimed to evaluate the actual risks and benefits of additional gastrectomy for upper third tumors. Methods We reviewed the clinicopathological data of patients who underwent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In this cohort, there are 5/42 (11.90%) cases with lymph node involvements revealed by surgical resection after non-curative ESD. Consistent with previous studies ( 13 , 26 ), our results show that the additional surgery group has a better prognosis in the long run. In clinical practice, the choice of treatment strategy is influenced by efficacy and risk of recurrence/metastasis, age, baseline physical condition, postoperative quality of life, patient or family preferences, and financial status.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this cohort, there are 5/42 (11.90%) cases with lymph node involvements revealed by surgical resection after non-curative ESD. Consistent with previous studies ( 13 , 26 ), our results show that the additional surgery group has a better prognosis in the long run. In clinical practice, the choice of treatment strategy is influenced by efficacy and risk of recurrence/metastasis, age, baseline physical condition, postoperative quality of life, patient or family preferences, and financial status.…”
Section: Discussionsupporting
confidence: 93%
“…Although this study only compared patient information for selecting surgical procedures, a recent meta-analysis of all available and most updated studies comparing ESD versus surgery for the treatment of uEGC found that all-cause mortality was similar in both groups after adjusted analyses ( 25 ). A recent South Korean study delved into the risks and advantages of extra surgery for upper third EGC post non-curative ESD, identifying lymphovascular invasion as the sole significant predictor of lymph node metastasis (P<0.001) ( 26 ). And a Japanese study that included 151 patients diagnosed with noncurative lesions after ESD treatment over the past decade recommended gastrectomy and lymph node dissection for patients with lymphatic vessel invasion and/or undifferentiated types ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with large diameter and multiple lesions are more likely to invade submucosa or even muscle layer, and there are more chances for the tumor cells to make contact with blood and lymphatic vessels, consequently, vessel invasion increases and regional LNM occurs. Similar to the above pathogenesis, the different surface area and distribution density of blood vessels and lymphatics between the stomach's different parts may lead to the different incidence of LNM 13,27 . Thus, the EDGC tumors located in the gastric antrum and pylorus region may be more prone to LNM than other sites.…”
Section: Discussionmentioning
confidence: 87%
“…Similar to the above pathogenesis, the different surface area and distribution density of blood vessels and lymphatics between the stomach's different parts may lead to the different incidence of LNM. 13,27 Thus, the EDGC tumors located in the gastric antrum and pylorus region may be more prone to LNM than other sites. The correlations between preoperative hypoalbuminemia or significant weight loss with LNM have not been reported.…”
Section: Discussionmentioning
confidence: 99%